P2.086 Origins of Repeat Infections with Chlamydia Trachomatis (Ct) Among Heterosexual Men in Two Southern Cities in the United States. (13th July 2013) - Kissinger, P; White, S; Schmidt, N; Taylor, S N; Mena, L; Lillis, R; Some, S; Defayette, K; Martin, D
Abstract : Background: Recent clinical trials have reported high repeat infection rates (12%–14%) following 1 g azithromycin. These data suggest that single-dose azithromycin may be inadequate, but high repeat infections rates could also be explained by exposure to an original or new partner or retesting before DNA clearance. The purpose of this study was to examine the origins of repeat CT infections among men. Methods: Men diagnosed with Ct by Gen-Probe Aptima Combo 2 at STD clinics in New Orleans, and Jackson, Mississippi were re-tested an average of 6 weeks after treatment with single-dose azithromycin. Detailed sexual behaviour histories were collected at baseline and follow-up via computer-assisted/self-administered interview and MLST genotyping was performed. Results: Of 367 men with Ct, 222 returned for a f/u visit [mean of 45 days post-baseline (s.d. 13)] and 14/217 (6.5%) were positive. Of the 14, 36% reported sexual re-exposure to a baseline partner, 14% reported sexual exposure to a new partner, 7% reported sexual exposure to both, and 43% denied sexual re-exposure. Thus far MLST genotyping completed for 3 baseline-f/up positive pairs. Two pairs with the same genotype (E/39) reported sexual re-exposure to a baseline partner and the pair with a new genotype reported sexual exposure to a new partner (D/19 to C/15). Conclusion: Early repeat infection rate among men with Ct in this study was lower than recently reported and about half could be explained by sexual re-exposure. Rates in the other two studies may have been inflated by high re-exposure rates or premature testing using NAAT since many of the participants were tested before 3 weeks. Studies that examine repeat infections should consider re-exposure/new exposure and retest when DNA clearance is assured. Our data does not support high treatment failure rates for 1 g azithromycin treatment of Ct.